Analysis of Design For Assembly (Dfa) in Exhaust Product Design - Hamzah Achmad Putra; Ribangun Bamban Jakaria (Procedia of Engineering and Life Science, 2021)
GRIP Exhaust is a small and medium industry which is engaged in manufacturing which produces mufflers. The production system in this company is to apply a production system made to order, where consumers can order exhaust products according to their requests. Designing exhausts according to technical specifications by applying the Design For Assembly (DFA) method and calculating the time required to assemble custom exhaust products into technical specifications by producing products according to user needs. With Design For Assembly (DFA) to make it easier and push time, but still focus on the function of the product itself and pay attention to the safety factor of its performance. custom stainless steel exhaust takes 2 hours to complete, rust-resistant quality, an efficiency value of 1.23, and has higher advantages and attractiveness in the eyes of consumers.